Childhood perfluoroalkyl substance exposure and executive function in children at 8 years. (October 2018) - Vuong, Ann M.; Yolton, Kimberly; Wang, Zhiyang; Xie, Changchun; Webster, Glenys M.; Ye, Xiaoyun; Calafat, Antonia M.; Braun, Joseph M.; Dietrich, Kim N.; Lanphear, Bruce P.; Chen, Aimin
Abstract: Background: Toxicological studies highlight the potential neurotoxicity of perfluoroalkyl substances (PFAS) during fetal development. However, few epidemiological studies have examined the impact of childhood PFAS on neurodevelopment. Methods: We employed data from 208 children in the Health Outcomes and Measures of the Environment Study, a birth cohort (Cincinnati, OH), to examine associations of six serum PFAS concentrations measured at 3 and 8 years with executive function assessed at 8 years using the validated parent-completed Behavior Rating Inventory of Executive Function survey. We used multiple informant models to identify susceptible windows of neurotoxicity to PFAS and executive function. We investigated trajectories of PFAS concentrations and whether sex modified these associations. Results: Each ln-increase in perfluorononanoate (PFNA) at 8 years was associated with a 3.4-point increase (95% CI 0.4, 6.3) in metacognition score, indicating poorer function. Children with PFNA above the median at 8 years had poorer global executive functioning compared to children with concentrations consistently below median levels (β = 6.5, 95% CI 0.2, 12.9). Higher concurrent PFNA was associated with poorer behavior regulation among males, while associations among females were null ( p PFNA × sex  = 0.018). Children with higher concurrent perfluorooctanoate (PFOA) had increased odds of being at risk of having clinical impairments in metacognition (OR = 3.18, 95% CI 1.17, 8.60). There were no associations between perfluorooctane sulfonate and perfluorohexane sulfonate and executive function. Conclusions: PFNA and PFOA at 8 years, but not 3 years, may be related to poorer executive function at 8 years. Results need to be confirmed in cohort studies with larger sample sizes. Highlights: PFAS concentrations at age 3 years were not associated with executive function at age 8 years. Concurrent PFNA was associated with impairments in metacognition and global executive function at 8 years. A sexually dimorphic relationship may be present, with males more sensitive to PFNA neurotoxicity. Childhood PFNA and PFOA, to a lesser extent, may be neurotoxic with regard to executive function.